Diabetic gastroparesis from autonomic neuropathy: surgical considerations and changes in vagus nerve morphology. Issue 7 (July 1984) - Guy, R J; Dawson, J L; Garrett, J R; Laws, J W; Thomas, P K; Sharma, A K; Watkins, P J
Abstract : Two cases with intractable vomiting due to gastroparesis, a rare feature of diabetic autonomic neuropathy, are described. Both required surgical treatment. In the first a gastroenterostomy was complicated by reflux gastritis requiring a revision operation; in the second a gastrojejunostomy was successful. Electron microscopic studies of the vagus nerve in one of the cases showed a severe reduction in the density of unmyelinated axons, the surviving axons tending to be of small calibre. The severity of the abnormalities supports the view that diabetic gastroparesis is related to vagal denervation.